HUBUNGAN TERPAAN INFORMASI PRODUK DAN TERPAAN PROMOSI PENJUALAN DENGAN KEPUTUSAN PEMBELIAN KEMBALI FASHION DI TOKOPEDIA - Gita Reza Nadhani; Nurist Surayya Ulfa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Fashion is one of the most searched and purchased categories by consumers in Tokopedia. Unfortunately, in the first quarter of 2023, Tokopedia got a very significant decrease in the number of visitors compared to the second quarter of 2022. This research aims to find out the relationship between exposure to product information and exposure to sales promotions and the decision to repurchase fashion at Tokopedia. The theory used cognitive process theory and behavioral learning theory. The sampling technique used purposive sampling with a total sample of 100 respondents. The analytical technique used Kendall Tau-b. The results of this research found that there was a positive and significant relationship between product information exposure (X1) and sales promotion exposure (X2) with the repurchase decision (Y) of fashion at Tokopedia with a weak correlation coefficient. The results of the research descriptively show that the intentional level of consumers in seeking about content and the usefulness is high. Unfortunately the level of consumer involvement in interacting with uploaded content is low. Tokopedia can change its social media marketing strategy which has a higher level of correlation coefficient. If Tokopedia still continue to use this strategy, they should make content which can increase consumer interaction.